Sorting out Business – Earn a Living During the Coronavirus Pandemic: Bachelor of Science in Business Administration - Garry Alfonsius (Universal Journal, 2020)
Every people choose how to open their business nowadays. Now most of in the world feels the impact of Covid – 19. Most of the company in the world they were fired a hundred until a thousand workers per day to make their company continue and escape from bankrupt. The income they got was lower than before Covid – 19. After they got fired from their company most of them to choose the alternate job like they work part time or they start small business for example food. In pandemic like this people choose to start food business because they will get more income than they choose another business. They can pay the tax every year and they only think about their business to make their business great and have a progress each year. But sometimes we can see another worker who they would not have a chance to have another job because they lack of knowledge or they do not have much money to start their small business. That is why they choose to idleness or we can say unemployment because they do not want to have another job or they want to have another job but the job of they want already got a limit so, they only have to wait to open recruitment.